Characterising and mapping potential and experienced tranquillity: from a state of mind to a cultural ecosystem service - Purves, RS; Wartmann, FM (Wiley, 2023)
Tranquil places that induce a sense of calm and peacefulness are important for those seeking respite from their stressful everyday lives. Although tranquillity is a word commonly used in everyday English, we show that its definition is complex, most often encompassing sight and hearing, with strong cultural and historical influences. To shed light on the concept of tranquillity and related research in geography and other disciplines, we (i) trace how tranquillity has been conceptualised and characterised (ii) outline how the potential for tranquillity has been modelled in Geographic Information Systems (GIS) and (iii) highlight methods capable of extracting individual experiences of tranquillity from interviews, public participation GIS and text analysis. We conclude by charting a research agenda for tranquillity that makes a case for theory development across disciplines including human geography, GIS, and environmental psychology, with interdisciplinary methodologies that should be implemented and developed to better reflect the importance of the combination of physical environment and lived human experience in shaping experienced tranquillity. Based on its importance for people's well-being, we argue for the recognition of tranquillity as a cultural ecosystem service in its own right. Finally, we call for a more holistic inclusion of tranquillity in policy-making and planning, where a focus on tranquillity and associated positive landscape and soundscape elements could help extend the focus beyond simply protection from noise, towards creating liveable and healthy environments for the future.